2021
DOI: 10.1016/j.bja.2020.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intramuscular tranexamic acid in bleeding trauma patients: a clinical trial

Abstract: Background: Intravenous tranexamic acid (TXA) reduces bleeding deaths after injury and childbirth. It is most effective when given early. In many countries, pre-hospital care is provided by people who cannot give i.v. injections. We examined the pharmacokinetics of intramuscular TXA in bleeding trauma patients. Methods: We conducted an open-label pharmacokinetic study in two UK hospitals. Thirty bleeding trauma patients received a loading dose of TXA 1 g i.v., as per guidelines. The second TXA dose was given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 25 publications
3
46
0
Order By: Relevance
“…However, the “translation” of whole blood TXA levels from VAMS capillary samples into plasma levels may require caution for high concentrations. The concentration range of the present study was less than 40 mg/L, corresponding to concentrations observed in pharmacokinetic studies with an intramuscular dose of 1 g or an oral dose of 2 g ( Grassin-Delyle et al, 2021a ; Grassin-Delyle et al, 2021b ). These pharmacokinetic studies with outpatient TXA use are precisely the types of studies for which design is most appropriate for the use of VAMS devices.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…However, the “translation” of whole blood TXA levels from VAMS capillary samples into plasma levels may require caution for high concentrations. The concentration range of the present study was less than 40 mg/L, corresponding to concentrations observed in pharmacokinetic studies with an intramuscular dose of 1 g or an oral dose of 2 g ( Grassin-Delyle et al, 2021a ; Grassin-Delyle et al, 2021b ). These pharmacokinetic studies with outpatient TXA use are precisely the types of studies for which design is most appropriate for the use of VAMS devices.…”
Section: Discussionsupporting
confidence: 50%
“…Although tranexamic acid (TXA) has been marketed for the prevention of bleeding since the 1960s and has been used in a range of surgical and out-of-hospital indications, the dosing regimens used are mostly empirical. High quality clinical trials with sufficient power to support efficacy in acute severe bleeding are relatively recent, as are the pharmacokinetic studies ( Collaborators, 2019 ; Collaborators et al, 2010 ; Woman Trial Collaborators, 2017 ; Grassin-Delyle et al, 2021a ; Grassin-Delyle et al, 2021b ; Grassin-Delyle et al, 2018 ; Grassin-Delyle et al, 2013a ). Timely TXA treatment, ideally within an hour of bleeding onset, has been shown to be essential for maximal efficacy in acute severe bleeding and so effective TXA blood concentrations must be achieved rapidly ( Collaborators et al, 2011 ; Gayet-Ageron et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective, pharmacokinetic study conducted in the emergency departments of two large London trauma centers has shown that intramuscular (IM) TXA is well tolerated and rapidly absorbed in bleeding trauma patients. 24 In this study, adult trauma patients who had received an IV 1-g TXA loading dose, either prehospital or in-hospital, were given the second TXA dose by IM injection. The IM dose was given as two 5 mL (0.5 g each) injections into the thigh (rectus femoris or vastus lateralis), gluteal, or deltoid muscles, depending on the clinical situation (e.g., the type of injury).…”
Section: Putting It All Together: What Should We Do For Trauma Victims?mentioning
confidence: 99%
“…[25,34] Recent research has found that TXA is well tolerated and rapidly absorbed after intramuscular injection reaching therapeutic concentrations within 15 minutes in bleeding trauma patients. [35] Further research is needed to assess the cost-effectiveness of different treatment thresholds and whether use of the BATT score and intramuscular TXA administration by paramedics increases the pre-hospital administration of TXA to patients at risk of bleeding from trauma. Prospective validation of the BATT score would certainly increase its value for clinical use.…”
Section: Relation To Other Studiesmentioning
confidence: 99%